Small Saving Schemes and Its Importance - WÓJCIK-CZERNIAWSKA Agnieszka; GRZYMAŁA Zbigniew (Communications of International Proceedings, 2022)
Public Provident Fund, Senior Citizens Savings Scheme, Post Office Recurring Deposit, and Sukanya Samriddhi Scheme are some of the government's investment vehicles for persons who wish to deposit little amounts over time as they earn. Small savings schemes are what they're called. Small Savings Schemes are a series of savings tools administered by the federal government to encourage residents of all ages to save consistently. The purpose of the paper is to pinpoint the different small saving schemes and their importance, and identify most important saving scheme. The public provident fund is the most safest and popular investment in India, PPF is a government-backed long-term saving scheme that is tax-free. They are attractive because they offer not just larger yields than bank fixed deposits, and also national assurance and tax advantages. These strategies ensure a high rate of return while reducing uncertainty. They can be set up in various forms, with monthly, quarterly, half-yearly, and yearly plans being the most common. Some of these plans might also help you save money on taxes.
Keywords: Saving Schemes; Tax; Government; Investment; Fixed Deposits